Adipose-derived stem cells derived decellularized extracellular matrix enabled skin regeneration and remodeling - Zhang, Jin; Xiang, Yang; Yang, Quyang; Chen, Jiqiu; Liu, Lei; Jin, Jian; Zhu, Shihui (Frontiers in Bioengineering and Biotechnology, 2024)
The tissues or organs derived decellularized extracellular matrix (dECM) carry immunogenicity and the risk of pathogen transmission, resulting in limited therapeutic effects. The cell derived dECM cultured in vitro can address these potential risks, but its impact on wound remodeling is still unclear. This study aimed to explore the role of decellularized extracellular matrix (dECM) extracted from adipose derived stem cells (ADSCs) in skin regeneration.ADSCs were extracted from human adipose tissue. Then we cultivated ADSC cells and decellularized ADSC-dECM for freeze-drying. Western blot (WB), enzyme-linked immunosorbent assay (ELISA) and mass spectrometry (MS) were conducted to analyzed the main protein components in ADSC-dECM. The cell counting assay (CCK-8) and scratch assay were used to explore the effects of different concentrations of ADSC-dECM on the proliferation and migration of human keratinocytes cells (HaCaT), human umbilical vein endothelia cells (HUVEC) and human fibroblasts (HFB), respectively. Moreover, we designed a novel ADSC-dECM-CMC patch which used carboxymethylcellulose (CMC) to load with ADSC-dECM; and we further investigated its effect on a mouse full thickness skin wound model.ADSC-dECM was obtained after decellularization of in vitro cultured human ADSCs. WB, ELISA and MS results showed that ADSC-dECM contained various bioactive molecules, including collagen, elastin, laminin, and various growth factors.CCK-8 and scratch assay showed that ADSC-dECM treatment could significantly promote the proliferation and migration of HaCaT, HUVEC, and HFB, respectively. To evaluate the therapeutic effect on wound healing in vivo, we developed a novel ADSC-dECM-CMC patch and transplanted it into a mouse full-thickness skin wound model.And we found that ADSC-dECM-CMC patch treatment significantly accelerated the wound closure with time. Further histology and immunohistochemistry indicated that ADSC-dECM-CMC patch could promote tissue regeneration, as confirmed via enhanced angiogenesis and high cell proliferative activity.In this study, we developed a novel ADSC-dECM-CMC patch containing multiple bioactive molecules and exhibiting good biocompatibility for skin reconstruction and regeneration. This patch provides a new approach for the use of adipose stem cells in skin tissue engineering.